Social Business Process Management and Knowledge Intensive Processes - Vesna Bosilj Vukšić; Dalia Suša; Anita Lovrić (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
Business process management (BPM) is a worldwide spread holistic management discipline which increases organizational performance by managing its business processes. A number of researchers indicate the need for further examination of the role of organizational culture in BPM and its maturity. In addition, there has been a recent development of social BPM as an effort to overcome the traditional BPM limitations by using social software for managing the organizations' business processes and increasing collaboration between BPM project teams. Therefore, we conducted a case study in one Croatian IT company which operates as a consultant company and deals with software implementation. Since their processes are knowledge intensive, they are not always formal and structured so social BPM helps the company with process change and optimization. The aim of this paper is to examine the role of organizational culture and social software usage on BPM maturity in the observed company
Keywords: M15; 330; social business process management; knowledge intensive processes; business process management maturity; organizational culture; society; case study; Croatia